A new severe plastic deformation method: thin-walled open channel angular pressing (TWO-CAP) - KENTLİ, AYKUT (SPRINGER LONDON LTD, 2020)
In this study, a novel severe plastic deformation method, named as thin-walled open channel angular pressing (TWO-CAP), was developed and applied to AZ31 magnesium alloy beams in U-type cross-sectional shape. First of all, the principles of the method with all parameters were determined, and the analytical model of the system was generated, and then the study was supported with the numerical analysis. Then, a proper experimental setup was established by considering theoretic outputs. After that, AZ31 magnesium alloy specimens were machined from bulk material in U-type shape as to fit the die channel, and then these specimens were annealed and pressed along the TWO-CAP die. Following the experimental studies, the specimens were tested in order to define the changes in mechanical and microstructural properties. In this stage, the tension test and hardness test were applied to determine the mechanical properties, while optical microscope, scanning electron microscope, energy dispersive spectrometry, X-ray diffraction, and transmission electron microscope analyses were applied to see the changes in microstructure. As a result, an improvement on strength, hardness, and toughness was observed depending on the changes on the microstructure and grain refinement due to the large plastic deformation.
Keywords: AZ31 magnesium alloy; Mechanical properties; Microstructure; SEM-EDS; SPD; TEM; XRD; AZ31 MAGNESIUM ALLOY; ULTRAFINE-GRAINED MATERIALS; MECHANICAL-PROPERTIES; MICROSTRUCTURAL EVOLUTION; HOMOGENEITY